Field Studies in Heritage Education: Assessing Impact on Tourism and Sustainability at Bujang Valley, Kedah, Malaysia - Adnan Jusoh, Miftachul Huda (Tanjung Malim, 2024)
Field Studies in Heritage Education: Assessing Impact on Tourism and Sustainability at Bujang Valley, Kedah, Malaysia by Adnan Jusoh, Miftachul Huda